KONVERSI SAMPAH ORGANIK DI LINGKUNGAN FMIPA UNIVERSITAS LAMPUNG MENJADI PUPUK ORGANIK CAIR (POC) DENGAN TEKNIK SOLUBLE LIQUID (SL) - Syaiful Bahri; John Hendri; Aspita Laila; Heri Satria; Yuli Ambarwati (Universitas Mataram, 2023)
One of the main problems faced by farmers in Lampung today is the limited or scarcity of subsidized fertilizers. Meanwhile, there is an interesting phenomenon that has occurred on campus, including at FMIPA, University of Lampung (Unila), that about waste. So far, organic waste in the Faculty of Mathematics and Natural Sciences, Unila, has not been utilized optimally. The organic waste is only collected and deposited at the Integrated Waste Management Site (TPST) at Unila to be sorted and then taken to the Final Disposal Site (TPA) of Bandar Lampung City. These conditions prompted us, as academics at the University of Lampung, to be moved to carry out a community service program with the theme